DBS of the PSA and the VIM in essential tremor: A randomized, double-blind, crossover trial. (7th August 2018) - Barbe, Michael T.; Reker, Paul; Hamacher, Stefanie; Franklin, Jeremy; Kraus, Daria; Dembek, Till A.; Becker, Johannes; Steffen, Julia K.; Allert, Niels; Wirths, Jochen; Dafsari, Haidar S.; Voges, Jürgen; et al.
Abstract : Objective: To evaluate deep brain stimulation (DBS) of the posterior subthalamic area (PSA) in essential tremor (ET) and compare it to the ventral intermediate nucleus of the thalamus (VIM) in terms of stimulation efficacy, efficiency, and side effects. Methods: DBS leads were implanted such that contacts were placed in the VIM, on the intercommissural line, and in the PSA. Thirteen patients with ET entered a randomized, double-blind crossover phase and completed a 1-year follow-up. Results: PSA-DBS significantly reduced tremor severity and improved quality of life. There were no relevant differences in quality and frequency of stimulation side effects between VIM and PSA, with a tendency toward greater tremor improvement with PSA stimulation. Clinical benefit was achieved at significantly lower stimulation amplitudes in the PSA. The majority of patients remained with PSA-DBS after 1 year. Conclusion: In accordance with previous retrospective investigations, our prospective data suggest that PSA-DBS is at least equally effective as but possibly more efficient than VIM-DBS. Classification of evidence: This study provides Class I evidence that for patients with essential tremor, PSA-DBS is not significantly different from VIM-DBS in suppressing tremor, but clinical benefit from PSA-DBS is attained at lower stimulation amplitudes.